TINJAUAN FILOSOFIS TENTANG PESERTA DIDIK DALAM PENDIDIKAN ISLAM - hakim, muhammad luqman (Qouman : Jurnal Pendidikan dan Studi Islam, 2025)
Education is conscious guidance and assistance provided by educators to students in accordance with their physical and spiritual development towards maturity. Learners in Islamic education have important aspects that need to be studied and developed in educational studies. This discussion explains the definition of learners in Islamic education, the needs of learners, the characteristics of learners, and the nature and code of ethics of learners in Islamic education. This study discusses a philosophical review of students in Islamic education by examining several pieces of literature. In this study, data was obtained from books and journals related to the philosophical review of students in Islamic education. References related to students in Islamic education refer to relevant books and journals. The results of the study explain the definition that, etymologically, students are pupils who receive teaching, while terminologically, they are pupils or individuals who are undergoing change and development and therefore still need guidance and direction in shaping their personalities and as part of the structural process of education. In other words, students are individuals who are undergoing a phase of development or growth, both physically and mentally as well as intellectually. The characteristics of students include: students are viewed as a unified human system and, in practice, are both the subject and object of education.